The Professor versus the Pastor - McLane, William W. (The biblical world, 1914)
It is highly desirable that the office of the pastor be not depreciated. The following article is a timely and vigorous presentation of the relation of the pastor to scholarship. The distinctions it makes are vital. If the minister is to treat his church as a class, he is bound to find that he will be tempted to substitute illumination for inspiration. He can well be scholarly, but he need not be a "scholar."